Mapping Out the “Wasteland”: Testimonies from the Serbian Commissariat for Refugees in the Service of Tudjman's Revisionism - Dulić, Tomislav (Holocaust and genocide studies, 2009)
In a 1989 monograph, Franjo Tudjman used reprints of witness statements by Serbian former inmates of Jasenovac concentration camp that depicted the Jewish prisoners in a negative light. A close examination of the original documents indicates that Tudjman used these highly problematic accounts of life in the camp uncritically. The descriptions of events contained in the statements do not always correspond to one another, and some are contradicted by other sources. The author of this article shows that a conflict emerged between some Jews and some Serbs in Jasenovac in March 1942, and suggests that this may explain in part why some of the Serbian refugees made negative remarks about “Jewish” behavior. Although Tudjman almost certainly was aware that the sources were problematic, he nevertheless used them—apparently, the author concludes, in an attempt to foster political support within segments of the Croatian nationalist diaspora in North America.